Covid‐19.bioreproducibility.org: A web resource for SARS‐CoV‐2‐related structural models. (8th October 2020) - Brzezinski, Dariusz; Kowiel, Marcin; Cooper, David R.; Cymborowski, Marcin; Grabowski, Marek; Wlodawer, Alexander; Dauter, Zbigniew; Shabalin, Ivan G.; Gilski, Miroslaw; Rupp, Bernhard; Jaskolski, Mariusz; Minor, Wladek
Abstract: The COVID‐19 pandemic has triggered numerous scientific activities aimed at understanding the SARS‐CoV‐2 virus and ultimately developing treatments. Structural biologists have already determined hundreds of experimental X‐ray, cryo‐EM, and NMR structures of proteins and nucleic acids related to this coronavirus, and this number is still growing. To help biomedical researchers, who may not necessarily be experts in structural biology, navigate through the flood of structural models, we have created an online resource, covid19.bioreproducibility.org, that aggregates expert‐verified information about SARS‐CoV‐2‐related macromolecular models. In this article, we describe this web resource along with the suite of tools and methodologies used for assessing the structures presented therein.